Low Loss W-Band Packaged Filtering Balun Based on a Modified Quarter-Mode Folded Substrate-Integrated Waveguide Cavity - Lixue Yang; Yang Yuan; Liang Zhou (IEEE Access, 2022)
A novel packaged filtering balun is proposed by modifying quarter-mode edge and diagonally folded SIW (FSIW) cavities. The TM220 mode is selected to realize the differential signal conversion by using a quarter-mode diagonally FSIW. Furthermore, TM130, and TM330 modes are obtained by using a quarter-mode edge FSIW cavity by analyzing the mode field distributions. A W band packaged filtering balun is designed and simulated. Then, it is fabricated with 70 $μ { m}$ thickness per layer based on our in- house Si-based MEMS photosensitive film process. The size of the filtering balun is only $2.83~λ \text{g}^{2}$ with insertion loss of 3 + 1.8 dB. These types of packaged filtering balun are very suitable for future 3D heterogeneous integration with other semiconductor devices.